2020
DOI: 10.1021/acssuschemeng.0c03419
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Fatty Acid-Based Amino Acid Ester as a New “Green” Hydrophobic Ionic Liquid for Drug Delivery

Abstract: Ionic liquid (IL)-based drug delivery systems have attracted considerable interest owing to their intrinsic tunability and ability to transport small or large molecules through the skin. However, the development of "green" ILs remains challenging. Herein, eight potentially "green" fatty acid-based amino acid ILs (FAAAE-ILs) were synthesized, and their potency in transdermal drug delivery was investigated using ibuprofen and a peptide drug. The synthesized ILs were characterized to evaluate their physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 57 publications
5
98
0
Order By: Relevance
“…It has been found that the hydrophobicity of common hydrophobic anions is in the order: [Tf 2 N] − > [PF 6 ] − > [C(CN) 3 ] − . 28 As for cations, amino acids are regarded as more environmentally friendly than imidazolium ILs, 29 so they were chosen as the cations of potential extractants, and further esterification was used to enhance their hydrophobicity. As a result, l -phenylalanine methyl ester bis(trifluoromethyl)sulfonimide ([PheC 1 ][Tf 2 N]), l -phenylalanine ethyl ester bis(trifluoromethyl)sulfonimide ([PheC 2 ][Tf 2 N]), glycine benzyl ester bis(trifluoromethyl)sulfonimide ([LeuC 2 ][Tf 2 N]), and l -leucine ethyl ester bis(trifluoromethyl)sulfonimide ([GlyOBzl][Tf 2 N]) were designed and screened through pilot experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the hydrophobicity of common hydrophobic anions is in the order: [Tf 2 N] − > [PF 6 ] − > [C(CN) 3 ] − . 28 As for cations, amino acids are regarded as more environmentally friendly than imidazolium ILs, 29 so they were chosen as the cations of potential extractants, and further esterification was used to enhance their hydrophobicity. As a result, l -phenylalanine methyl ester bis(trifluoromethyl)sulfonimide ([PheC 1 ][Tf 2 N]), l -phenylalanine ethyl ester bis(trifluoromethyl)sulfonimide ([PheC 2 ][Tf 2 N]), glycine benzyl ester bis(trifluoromethyl)sulfonimide ([LeuC 2 ][Tf 2 N]), and l -leucine ethyl ester bis(trifluoromethyl)sulfonimide ([GlyOBzl][Tf 2 N]) were designed and screened through pilot experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, ILs are under the spotlight of the latest research on DTD of therapeutic peptides. For instance, Goto and co-workers developed hydrophobic fatty acid/amino ester-based ILs that were liquid at room temperature (i.e., RTILs) and fully miscible with common CPEs, such as isopropyl myristate (IPM) [ 168 ]. Formulations comprising 10% wt of the RTILs in IPM showed lower cytotoxicity than the standard CPE sodium lauryl sulfate and being also able to better permeate a NSAID (ibuprofen) than the conventional CPE Transcutol ® .…”
Section: Ionic Liquid-based Approaches In Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…Formulations comprising 10% wt of the RTILs in IPM showed lower cytotoxicity than the standard CPE sodium lauryl sulfate and being also able to better permeate a NSAID (ibuprofen) than the conventional CPE Transcutol ® . These formulations (especially the L-proline ethyl ester linoleate-based one), enhanced the percutaneous permeation of an antigenic peptide accross porcine skin [ 168 ]. The same authors have very recently used similar fatty acid-based ILs to formulate IL-in-oil nanodispersions that were optimized for higher physicochemical stability, as well as increased loading capacity and in vivo transdermal delivery of the anticancer nonapeptide leuprolide [ 169 ].…”
Section: Ionic Liquid-based Approaches In Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…ILs were shown to enhance transdermal permeation through mechanisms involving disruption of cell integrity, lipid fluidization and extraction, and several reports on their use in topical emulsions to promote drug solubility and permeation are available [ 115 , 116 , 117 ]. Recently, Moshikur, R and co-workers (2020) developed a new family of IL-based on fatty acids and amino acid esters [ 118 ]. Fatty acids and amino acid esters are well-known potent CPEs with low cytotoxicities.…”
Section: Amino Acid-based Enhancersmentioning
confidence: 99%